Predictors of outcomes in patients with type 2 diabetes in the lixisenatide GetGoal clinical trials. Issue 2 (29th November 2016) - Blonde, Lawrence; Chava, Pavan; Dex, Terry; Lin, Jay; Nikonova, Elena V.; Goldenberg, Ronald M.
Abstract : Aims: To explore the treatment outcomes in adult patients with type 2 diabetes (T2D) enrolled in the GetGoal trials of lixisenatide (LIXI), and the predictive effects of baseline characteristics on outcomes. Methods: This study was a pooled analysis of patient‐level data from the LIXI GetGoal studies comparing LIXI and placebo. Patients were divided into baseline therapy groups: those receiving oral antidiabetes drugs (OADs) at baseline (n = 2760) or those receiving basal insulin at baseline (n = 1198). Results: Compared with placebo, LIXI treatment led to significantly greater reductions in glycated haemoglobin (HbA1c), and greater achievement of the composite endpoint of HbA1c <7.0% (53 mmol/mol) with no symptomatic hypoglycaemia and no weight gain in either the OAD (34% vs 18%; P < .0001) or the basal insulin groups (19% vs 10%; P < .0001). Treatment with LIXI was associated with a greater percentage of patients experiencing a symptomatic hypoglycaemic event compared with placebo in both the OAD (5% vs 3%; P = .0098) and basal insulin groups (27% vs 17%; P < .0001). In assessing baseline factors that were predictors of treatment outcomes, only baseline HbA1c and LIXI treatment were strong predictors of outcomes in both the OAD and basal insulin groups. No other baseline characteristic had such a large or consistent clinically relevant predictive effect across treatment outcomes. Conclusions: The results from this study show that irrespective of baseline characteristics, LIXI treatment, as an add‐on to OAD or basal insulin therapy, is effective in reducing HbA1c and achieving composite endpoints.